Clinical and treatment factors associated with the mortality of COVID-19 patients admitted to a referral hospital in IndonesiaResearch in context - Yovita Hartantri; Josephine Debora; Leonardus Widyatmoko; Gezy Giwangkancana; Hendarsyah Suryadinata; Evan Susandi; Elisabeth Hutajulu; Assica Permata Amalya Hakiman; Yesy Pusparini; Bachti Alisjahbana (Elsevier, 2023)
Summary: Background: Indonesia had the second-highest number of COVID-19 cases and deaths in South-East Asia. We aimed to determine the factors associated with this mortality and the effect of the recommended COVID-19 treatment regimen during the first 10 months of the epidemic. Methods: This was a retrospective cohort study using secondary data from medical records. In total, 689 adult COVID-19 inpatients hospitalized between March and December 2020 were enrolled. Clinical characteristics, laboratory parameters, and treatments were analyzed by survival outcome. Kaplan-Meier statistics were used to estimate survival. Findings: Of the 689 patients enrolled, 103 (14.9%) died. Disease severity was highly associated with mortality (hazard ratio [HR]: 7.69, p < 0.001). Other clinical factors associated with mortality were older age and comorbidities. Based on laboratory parameters, higher procalcitonin and C-reactive protein contents and a neutrophil-to-lymphocyte ratio >3.53 were also linked to mortality. Favipiravir was associated with lower mortality, with adjusted HRs of 0.24 (0.11-0.54) and 0.40 (0.17-0.98) among the mild/moderate and severe cases, respectively. Among patients with severe disease, steroids showed some beneficial effects in the early days of hospitalization. Interpretation: Older age and comorbidities were associated with disease severity and, consequently, higher mortality. Higher mortality after the second week of hospitalization may be related to secondary bacterial infection. Favipiravir showed significant benefit for COVID-19 survival, while steroids showed benefit only in the early days of admission among patients with severe disease. Funding: This research did not receive a specific grant from any funding agency in the public, commercial, or not-for-profit sectors.